An implementation strategy package (video education, HIV self-testing, and co-location) improves PrEP implementation for pregnant women in antenatal care clinics in western Kenya - Sila, Joseph; Wagner, Anjuli D.; Abuna, Felix; Dettinger, Julia C.; Odhiambo, Ben; Ngumbau, Nancy; Oketch, George; Sifuna, Enock; Gómez, Laurén; Hicks, Sarah; John-Stewart, Grace; Kinuthia, John (Frontiers in Reproductive Health, 2023)
Background: Pre-exposure prophylaxis (PrEP) is recommended by the World Health Organization and Kenyan Ministry of Health for HIV prevention in pregnancy and postpartum for women at risk for HIV. Integration of PrEP into antenatal care is promising, but delivery gaps exist in the face of health care provider shortages in resource-limited settings. Methods: Between May-November 2021, we conducted a difference-in-differences study (3 months pre- and 3 months post-; 4 intervention and 4 comparison facilities). We tested a combination of 3 implementation strategies – video-based PrEP information in the waiting bay, HIV self-testing, and dispensing of PrEP in the antenatal care rooms – to improve PrEP delivery. We compared absolute changes in: proportion of antenatal attendees screened for PrEP (PrEP penetration), proportion receiving all PrEP-specific steps in a visit (HIV testing, risk screening, PrEP counseling) (PrEP fidelity), client PrEP knowledge, client satisfaction, and waiting time and service time (a priori outcomes); post hoc we compared the proportion offered PrEP (PrEP offer) and completing HIV testing. We measured provider perceptions of acceptability and appropriateness of the implementation strategies. Results: We observed significant improvements in PrEP penetration, PrEP offer, satisfaction, and knowledge (p<0.05) and improvements in fidelity that trended towards significance (p=0.057). PrEP penetration increased 5 percentage points (p=0.008), PrEP fidelity increased 8 percentage points (p=0.057), and PrEP offer increased 4 percentage points (p=0.003) in intervention vs comparison facilities. Client PrEP knowledge increased 1.7 out of 7 total points (p<0.001) and client satisfaction increased 0.7 out of 24 total points (p=0.003) in intervention vs comparison facilities. We observed no changes in service time (0.09 minute decrease; p=0.435) and a small increase in waiting time (0.33 minute increase; p=0.005). HIV testing among those eligible did not change (1.5 percentage point decrease, p=0.800). Providers felt the implementation strategies were acceptable and appropriate (median acceptability: 20/20; median appropriateness: 19.5/20). However, absolute levels of each step of the PrEP cascade remained suboptimal. Conclusions: An implementation strategy package with video information, HIV self-testing, and co-location of medication dispensing enhanced PrEP delivery across several implementation outcomes and client satisfaction while not substantially increasing wait time or decreasing provider-client contact